MicroRNA-10b controls the metastasis and proliferation of colorectal cancer cells by regulating Krüppel-like factor 4 - Yue Xie; Jing Zhao; Yanling Liang; Min Chen; Yihong Luo; Xiaobing Cui; Bo Jiang; Liang Peng; Xinying Wang (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
Mir-10b has been reported as a key regulator of metastasis in many human tumours. Moreover, it has also been regarded as a prognostic marker and therapeutic target of colorectal cancer (CRC). Whether miR-10b could affect the metastasis and proliferation of CRC is unclear. MiR-10b expression was detected by qPCR in human CRC tissues and cell line, Luciferase activity was employed for miR-10b binding to the 3`UTR of KLF4, Genes expression were examined by western blot, and mRNA by qPCR. PI and Annexin V staining were used to evaluate the cell cycle and apoptosis. Cell proliferation was detected with MTT, and cell migration and invasion were performed with Transwell assay. We found that miR-10b expression was up-regulated in metastatic CRC tissues and cell lines. Inhibition of miR-10b prevented cancer cell metastasis and growth by inducing cell-cycle arrest and apoptosis in vitro. Moreover, we found that KLF4 was a direct target of miR-10b. MiR-10b inhibitor led to the up-regulation of E-cadherin expression and the down-regulation of cyclin D1, which were partly abrogated after silencing KLF4.